Sound and Image : Aesthetics and Practices. - Knight-Hill, Andrew (Sound Design, 2020)
Sound and Image: Aesthetics and Practices brings together international artist scholars to explore diverse sound and image practices, applying critical perspectives to interrogate and evaluate both the aesthetics and practices that underpin the audiovisual. Contributions draw upon established discourses in electroacoustic music, media art history, film studies, critical theory and dance; framing and critiquing these arguments within the context of diverse audiovisual practices. The volume's interdisciplinary perspective contributes to the rich and evolving dialogue surrounding the audiovisual, demonstrating the value and significance of practice-informed theory, and theory derived from practice. The ideas and approaches explored within this book will find application in a wide range of contexts across the whole scope of audiovisuality, from visual music and experimental film, to narrative film and documentary, to live performance, sound design and into sonic art and electroacoustic music. This book is ideal for artists, composers and researchers investigating theoretical positions and compositional practices which bring together sound and image.